2017
DOI: 10.1038/s41598-017-12998-w
|View full text |Cite
|
Sign up to set email alerts
|

Increased NK cell immunity in a transgenic mouse model of NKp46 overexpression

Abstract: Natural Killer (NK) cells employ activating receptors like the Natural Cytotoxicity Receptors (NCRs: NKp30, NKp44 and NKp46), of which only NKp46 has a mouse orthologue (Ncr1), to eliminate abnormal cells. NKp46/Ncr1 is considered a selective marker for NK cells, although it is also found on a subset of ILCs, where it appears to be without function. The influenza virus hemagglutinin (HA) was the first ligand identified for Ncr1/NKp46 followed by other viral, bacterial and even fungal ligands. NKp46/Ncr1 also r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 59 publications
1
13
0
Order By: Relevance
“…We also observed a downmodulation of NKp46 upon IL-15 exposure. This is in accordance with previous reports (50) and is troublesome, given the importance of this receptor in NK cell antiviral activity (22,51,52). Therefore, and even if we observed an important improvement in NK cell function despite NKp46 downmodulation, it might be of interest to consider a complementary strategy to boost NKp46 expression, thus further increasing NK cell antiviral function.…”
Section: Discussionsupporting
confidence: 92%
“…We also observed a downmodulation of NKp46 upon IL-15 exposure. This is in accordance with previous reports (50) and is troublesome, given the importance of this receptor in NK cell antiviral activity (22,51,52). Therefore, and even if we observed an important improvement in NK cell function despite NKp46 downmodulation, it might be of interest to consider a complementary strategy to boost NKp46 expression, thus further increasing NK cell antiviral function.…”
Section: Discussionsupporting
confidence: 92%
“…For example, genetic deficiency of NKp46 in mice results in the impaired clearance of subcutaneous T lymphoma (95) and melanoma (96) tumors and melanoma lung metastases (97, 98). Moreover, transgenic overexpression of NKp46 resulted in the enhanced clearance of melanoma lung metastases (99). Intriguingly, enhanced NKp46 signaling elicited IFN-γ secretion and increased tumor deposition of fibronectin, which altered the solid tumor architecture and resulted in the decreased formation of melanoma metastases (100).…”
Section: Ncrs and Their Ligands In Cancermentioning
confidence: 99%
“…However, it is also possible that the NCRs may regulate other anti-tumor pathways. For melanoma metastases, NK cells were attributed to play a major role (99). However, ILC1 are phenotypically closely related to conventional NK cells as both these cell-types express T-bet and secrete IFN-γ (132, 133).…”
Section: Ncr-mediated Control Of Tumoricidal Pathwaysmentioning
confidence: 99%
“…It is well established that activated NK cells destroy tumor cells mainly via cytotoxicity effector molecules, including granzyme B, perforin, IFN-γ and TNF-α ( 28 ). The results of flow cytometry revealed that the expression of granzyme B and IFN-γ was significantly increased following incubation with propofol ( Fig.…”
Section: Resultsmentioning
confidence: 99%